An Inventory of the Sand Flies (Diptera: Psychodidae) of Rudbar County, a New Focus of Leishmaniasis in Northern Iran, with a Taxonomic Note on the Subgenus Larroussius - Behzad Norouzi; Ahmad Ali Hanafi-Bojd; Vahideh Moin-Vaziri; Ayoob Noorallahi; Shahyad Azari-Hamidian (Tehran University of Medical Sciences, 2020)
Background: Different forms of leishmaniasis are significant infectious diseases in Iran. While, Rudbar County of Guilan Province has been introduced as a new cutaneous leishmaniasis focus, there are few published data about the phlebotomine sand flies (Diptera: Psychodidae) of the province. Methods: To study the phlebotomine fauna of Rudbar County, the sampling was performed in 12 collection sites by light traps, sticky traps and manual aspirators throughout August-December 2015. Sand flies were removed from the sticky traps, rinsed in acetone and stored in 80% ethanol along with the collections of light traps and hand catches. Results: In total, 2186 sand flies were collected and ten species representing two genera were morphologically identified: Phlebotomus (Adlerius) halepensis (0.27%), Ph. (Larroussius) kandeladii (0.10%), Ph. (Lar.) neglectus (0.91%), Ph. (Lar.) perfiliewi (53.88%), Ph. (Lar.) tobbi (43.45%), Ph. (Paraphlebotomus) sergenti (0.82%), Ph. (Phlebotomus) papatasi (0.10%), Sergentomyia (Parrotomyia) baghdadis (0.27%), Se. (Sintonius) clydei (0.05%), Se. (Sin.) tiberiadis (0.10%). The species Ph. halepensis, Ph. neglectus, Ph. perfiliewi, Se. baghdadis, Se. clydei and Se. tiberiadis were reported for the first time in Guilan Province. This study also verified the presence of Ph. neglectus (Ph. major krimensis as a synonym and morphotype) in Iran. Moreover, the taxonomy of the subgenus Larroussius of the province was discussed. Conclusion: The prevalence of suspected or proven cutaneous and visceral leishmaniasis vectors is noteworthy. The study of ecology of sand flies and detecting the exact vectors of leishmaniasis and phlebotomine fever by molecular specific tests in Guilan Province are recommended.